Flexible Articulation of Open Recognition (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Based on the work of Canadian and international clients such as the Inter-American Development Bank, International Training Centre of the ILO (ITCILO), and the Civics Credentialing System in the U.S., Learning Agents has developed a shareable framework to help organizations get started with open recognition. The Learning Agents Flexible Recognition Framework spans a spectrum of formality from formal to informal, using the presence or absence of summative assessment as one of several rough guidelines for high-level differentiation of badge types. Other criteria include organized versus experiential and self-directed learning, alignment to standards, such as for certificates or certifications, the presence or absence of evidence, application of learning, observed performance, peer recognition, and self-assertion. Depending on the level of formality and nature of support, these types of recognition can provide assurance and "rigor" at the formal end of the spectrum or appreciation and learner empowerment at the informal end of the spectrum. The 2025 poster is an updated version of this evolving framework, which was last shared at ePIC 2024. The 2025 version recently informed the implementation of custom extensions to the Achievement field of Open Badges v3, by Open Badge Factory, and CanCred. It also informed (and is being informed by) other standards in development, such as the Canadian Standards Association (CSA) Group's Canadian framework for microcredential meta-data. The Learning Agents Flexible Recognition Framework is now being maintained at learningagents.ca. Keywords: open recognition, Flexible Recognition Frameworks, digital credentials, Open Badges v3, microcredential metadata, summative assessment, formal and informal learning